Functionality Improvement of Gemfibrozil Formulations by QbD Approach - A, Mukharya (Journal of Medical Biomedical and Applied Sciences, 2014)
Die fill problem is encountered in production batches if the flow of the blend is not optimum. The flow of the blend is related to the characteristics of granules. The aim of this study was to formulate solid dosage form of gemfibrozil. Gemfibrozil is a waxy, crystalline, hydrophobic material that results in prolongation of disintegration time during storage in stability studies. Because of the fluffy nature of API flow problem was also encountered. Product and process characteristics important to desired performance must be derived from combination of prior knowledge and experimental assessment during product development, which is re-quired to achieve objectives of Quality by Design (QbD). From prior knowledge and experimental data, a multivariate model link-ing product and process measurements and desired attributes was constructed. Flow of gemfibrozil blend was improved by addi-tion of colloidal silicone dioxide, selecting microcrystalline cellulose of higher particle size and by producing granules of suffi-cient strength. Since the major portion of the tablet was gemfibrozil, the role of particle characteristics was also investigated.